2021
DOI: 10.1017/jfm.2021.756
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization-based design of microstructured membranes: wake flows past permeable shells

Abstract: A formal framework to characterize and control/optimize the flow past permeable membranes by means of a homogenization approach is proposed and applied to the wake flow past a permeable cylindrical shell. From a macroscopic viewpoint, a Navier-like effective stress jump condition is employed to model the presence of the membrane, in which the normal and tangential velocities at the membrane are respectively proportional to the so-called filtrability and slip numbers multiplied by the stresses. Regarding the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 75 publications
5
22
0
Order By: Relevance
“…For and , the average velocity across the membrane is and thus the Reynolds number referred to this velocity and to the rectangle size is . Hence, the assumption of negligible inertia is reasonable for the considered cases of and Reynolds number (Nield & Bejan 2013), already shown in Ledda et al (2021) for the two-dimensional case and confirmed by the reasonable agreement of this section. Thanks to the generality of the homogenized model (2.3), the same value of permeability can be obtained by tuning the value of with a different geometry, e.g. by reducing the height of the rectangle one can obtain larger permeabilities and thus reduce the value of , improving the accuracy of the method at large permeabilities.…”
Section: Figure 11supporting
confidence: 81%
See 4 more Smart Citations
“…For and , the average velocity across the membrane is and thus the Reynolds number referred to this velocity and to the rectangle size is . Hence, the assumption of negligible inertia is reasonable for the considered cases of and Reynolds number (Nield & Bejan 2013), already shown in Ledda et al (2021) for the two-dimensional case and confirmed by the reasonable agreement of this section. Thanks to the generality of the homogenized model (2.3), the same value of permeability can be obtained by tuning the value of with a different geometry, e.g. by reducing the height of the rectangle one can obtain larger permeabilities and thus reduce the value of , improving the accuracy of the method at large permeabilities.…”
Section: Figure 11supporting
confidence: 81%
“…When and , the fluid can flow through the membrane but cannot slip tangentially. However, such a situation is unlikely to happen since actual permeable microstructures are always characterized by non-zero values of permeability and slip (Ledda et al 2021).…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations